Gender disparities in chemotherapy use and survival in patients with advanced bladder cancer - Rose, Tracy L. (Cancer, 2016)
BACKGROUND: Women with advanced bladder cancer have inferior survival compared to men. However, women treated on clinical trials do not have a survival disadvantage. Less frequent administration of systemic chemotherapy in women with advanced bladder cancer may contribute to their inferior survival. METHODS: We identified patients with stage IV bladder cancer from 1998–2010 using the National Cancer Data Base (NCDB), a national outcomes database that includes 70% of all newly diagnosed cancer cases in the United States. Gender differences in demographics, systemic chemotherapy administration, and overall survival (OS) were compared. RESULTS: 23,981 patients were identified (35% female). Compared with men, women were older, more likely to be black, and less likely to be insured (p<0.01 for all). Charlson Deyo comorbidity score did not differ between men and women. Women were less likely to receive systemic chemotherapy than men (45% vs 52%, adjusted RR 0.91 [95% CI 0.88–0.94]). Women had a lower median OS compared to men (8.0 months (95% CI 7.7–8.3) vs 9.8 months (95% CI 9.5–10.0), p<0.001). OS remained lower for women on multivariable analysis, even after adjusting for administration of systemic chemotherapy (HR for death 1.11 [95% CI 1.08–1.15]. CONCLUSIONS: Women are less likely than men to receive systemic chemotherapy for advanced bladder cancer and this difference may partially account for poorer OS in women. However, OS remains lower in women independent of chemotherapy use, and may be related to unmeasured comorbidities, functional status, or tumor biology.